Preference changes among american youth : Family, work, and goods aspirations, 1976-86 - Crimmins, E. M.; Easterlin, R. a.; Saito, Y.
tbls.
pp. 115-133
Keywords: Estados Unidos de America; Jovenes; Familia; Trabajo; Tiempo Libre; Condición Social